Lymphocyte receptors for pertussis toxin. - Clark, C G (1990)
We have investigated human T-lymphocyte receptors for pertussis toxin by affinity isolation and photoaffinity labeling procedures. T lymphocytes were obtained from peripheral human blood, surface iodinated, and solubilized in Triton X-100. The iodinated mixture was then passed through pertussis toxin-agarose, and the fractions were analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Autoradiography of the fixed, dried gels revealed several bands in the pertussis toxin-bound fraction that were not observed in fractions obtained from histone or fetuin-agarose. Further investigations employed a photoaffinity labeling reagent, sulfosuccinimidyl 2-(p-azido-salicylamido)-1,3'-dithiopropionate, to identify pertussis toxin receptors in freshly isolated peripheral blood monocytic cells, T lymphocytes, and Jurkat cells. In all three cell systems, the pertussis toxin affinity probe specifically labeled a single protein species with an apparent molecular weight of 70,000 that was not observed when the procedure was performed in the presence of excess unmodified pertussis toxin. A protein comparable in molecular weight to the one detected by the photoaffinity labeling technique was also observed among the species that bound to pertussis toxin-agarose. The results suggest that pertussis toxin may bind to a 70,000-Da receptor in human T lymphocytes.